IPTEKS SPT MASA PAJAK PERTAMBAHAN NILAI (PPN) PADA PT CIPUTRA INTERNASIONAL CABANG MANADO - Mantiaha, Arisna J.; Mintalangi, Syermi (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Tax is a contribution from the people to the country. Every taxable entrepreneurs report tax reports to the government. One of them is Value Added Tax (VAT). PT Ciputra Internasional Manado report it’s Periodic Tax Return of VAT using e-Invoice provided by the Director General Tax. E-Invoice own application used by taxable entrepreneur in carrying out tax obligation. This study wants to provide knowledge in the application of e-Invoice to reporting VAT’s periodic tax return. Result of this research showed that PT Ciputra Internasional Manado in reporting Periodic Tax Return of VAT compliance with UU No.42 of 2009, Director General of Tax Regulation No. PER-31/PJ/2017, and Director General of Tax Regulation No. PER-01/PJ/2017.Keywords : Value Added Tax, Reporting, E-Invoice